INTEGRATION OF THE CUBAN BOXING SCHOOL INTO THE NATIONAL SYSTEM OF SPORTS TRAINING OF HIGHLY SKILLED BOXERS OF UZBEKISTAN: THEORY AND PRACTICE - POLATOV Saken Dzhetibaevich («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
The article discusses the specifics of training the national boxing team of Uzbekistan with an emphasis on integrat- ing the Cuban school into the existing national training system. The study included a detailed study of the successive phases of training macrocycles, the methods used for physical improvement and technical and tactical skills of boxers, and an analysis of the competitive results achieved by athletes at the level of major international competitions. Empiri- cal data confirm the high degree of effectiveness of the integrated training model used and reveal a stable dynamic of positive growth in the achievements of Uzbek boxers on the world stage